Emerging microfluidic and biosensor technologies for improved cancer theranostics - Caballero, David (2022)
Microfluidics and biosensors have already demonstrated their potential in cancer research. Typical applications of microfluidic devices include the realistic modeling of the tumor microenvironment for mechanistic investigations or the real-time monitoring/screening of drug efficacy. Similarly, point-of-care biosensing platforms are instrumental for the early detection of predictive biomarkers and their accurate quantification. The combination of both technologies offers unprecedented advantages for the management of the disease, with an enormous potential to contribute to improving patient prognosis. Despite their high performance, these methodologies are still encountering obstacles for being adopted by the healthcare market, such as a lack of standardization, reproducibility, or high technical complexity. Therefore, the cancer research community is demanding better tools capable of boosting the efficiency of cancer diagnosis and therapy. During the last years, innovative microfluidic and biosensing technologies, both individually and combined, have emerged to improve cancer theranostics. In this chapter, we discuss how these emerging-and in some cases unconventional-microfluidics and biosensor technologies, tools, and concepts can enhance the predictive power of point-of-care devices and the development of more efficient cancer therapies.